IMPLEMENTASI PERATURAN MENTERI AGRARIA DAN TATA RUANG/KEPALA BADAN PERTANAHAN NASIONAL NOMOR 13 TAHUN 2017 TENTANG TATA CARA BLOKIR DAN SITA PADA KANTOR PERTANAHAN KOTA BANDAR LAMPUNG - Sholin Erbin Mart Rajagukguk; Lintje Anna Marpaung; Herlina Ratna Sumbawa Ningrum (Law Faculty of Universitas Bandar Lampung, 2019)
According to regulation of the Minister of Agrarian and the spatial/Head of national Land Agency No. 13 of 2017 concerning the block and Confiscation procedure, the registration is the administrative action of the head of the land office or the appointed official to establish State of the status quo (freezing) on land rights that are provisional to the Act and legal events of the land, while the recording of the seized is the administrative action of the head of the land office or the appointed officer to Record any seized from judicial institutions, investigators or other competent institutions. This writing problem is how the implementation of regulation of the Minister of Agrarian and Spatial/Head of national Land Agency No. 13 of 2017 about procedure block and Confiscation at the Land office of Bandar Lampung. The implementation of the regulation of the Minister of Agrarian and Spatial/Head of national Land Agency number 13 year 2017 about the procedure of block and Confiscation at the Land Office of Bandar Lampung is not currently implemented in the maximum Because it is still not in sync between regulation of the Minister of Agrarian and the spatial/Head of national Land Agency No. 13 of 2017 about procedures for blocking and Confiscation with the application for land services efforts.